2005
DOI: 10.1002/bsl.669
|View full text |Cite
|
Sign up to set email alerts
|

Figuring out la femme fatale: conceptual and assessment issues concerning psychopathy in females

Abstract: Despite the growing number of studies on psychopathy in females, the core characteristics of this personality disorder among females remain uninvestigated. Most studies on psychopathy in females have attempted to understand the disorder by applying male criteria to adult females: they have ignored putative gender differences in the constitution and expression of this disorder. Several issues require resolution: first, whether practitioners apply the same criteria to diagnose psychopathy in women, second, wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(131 citation statements)
references
References 78 publications
(85 reference statements)
5
123
0
3
Order By: Relevance
“…Thus, evidence suggests that psychopathy may be expressed differently amongst female offenders in comparison to their male counterparts (Forouzan & Cooke, 2005;Hamburger, Lilienfeld, & Hogben, 1996;Nicholls, Ogloff, Brink, & Spidel, 2005;Sevecke, Lehmkuhl, & Krischer, 2009;Vitale, Smith, Brinkley, & Newman, 2002). Finally, investigations to explore gender differences with regards to sexual aggression in psychopathic non-offenders are seemingly non-existent.…”
mentioning
confidence: 99%
“…Thus, evidence suggests that psychopathy may be expressed differently amongst female offenders in comparison to their male counterparts (Forouzan & Cooke, 2005;Hamburger, Lilienfeld, & Hogben, 1996;Nicholls, Ogloff, Brink, & Spidel, 2005;Sevecke, Lehmkuhl, & Krischer, 2009;Vitale, Smith, Brinkley, & Newman, 2002). Finally, investigations to explore gender differences with regards to sexual aggression in psychopathic non-offenders are seemingly non-existent.…”
mentioning
confidence: 99%
“…Consistent with previous research on psychopathy and gender, the current study found that males possessed higher levels of primary psychopathy than females, but that secondary psychopathy did not differ between genders (Miller, Gaughan, & Pryor, 2008). Although the gender difference in primary psychopathy found in the current study produced a small effect, this finding provides some support for claims by clinicians that the interpersonal and affective features of psychopathy are muted in women (Forouzan & Cooke, 2005). However, alternative explanations for this difference have been proposed in detail by Forouzan and Cooke (2005), including, effects of gender socialisation on both the behavioural expression of psychopathy in females, and the clinicians' assessment of psychopathy in females; the failure of current psychopathy assessments, designed for males, to capture female psychopathy; and genuine differences in symptomatology for females.…”
Section: Key Findingssupporting
confidence: 89%
“…Although the gender difference in primary psychopathy found in the current study produced a small effect, this finding provides some support for claims by clinicians that the interpersonal and affective features of psychopathy are muted in women (Forouzan & Cooke, 2005). However, alternative explanations for this difference have been proposed in detail by Forouzan and Cooke (2005), including, effects of gender socialisation on both the behavioural expression of psychopathy in females, and the clinicians' assessment of psychopathy in females; the failure of current psychopathy assessments, designed for males, to capture female psychopathy; and genuine differences in symptomatology for females. In addition to gender differences in mean psychopathy scores, the current study also found a range of gender differences in the relationships between psychopathy and criminal attitudes, and psychopathy and self-reported criminal behaviour.…”
Section: Key Findingssupporting
confidence: 73%
See 2 more Smart Citations